A Test of the Horvath–Kawazoe Method by Monte Carlo Simulation - D. Valladares; G. Zgrablich (Adsorption Science & Technology, 1997)
The Horvath–Kawazoe (H–K) method, which is frequently used to obtain the micropore size distributions of microporous materials, has been tested by Monte Carlo Simulation of nitrogen adsorption isotherms. The results show that the H–K method only gives good results when the microporosity is confined to a pore size lower than approximately 13 Å. In this region, although the method can predict the micropore size distribution peak with acceptable precision, it fails for wider distributions.